MATHEMATICS AND LITERATURE: THE POTENTIALITIES OF DIGITAL TECHNOLOGIES IN BUILDING STORIES - Brum, Aline de Lima; Pereira, Elaine Corrêa (Cadernos de Educação Tecnologia e Sociedade, 2019)
This article presents a review of a master 's research carried out with the ninth-grade students of elementary school from a Brazilian public school, in which students' perceptions about the potential of digital technologies in Mathematics teaching and learning were examined. In this sense, we developed pedagogical practices of mathematical research using digital technologies, as well as the use of smartphones in the production of videos, the construction of conjectures with the GeoGebra software and the recognition of Literature as an educational didactic resource in Mathematics classes. For the analysis of the data we adopted the Discursive Textual Analysis method because it is a qualitative approach and allows the understanding of the phenomenon investigated in the educational environment. The results showed that the inclusion of Literature and smartphone in Mathematics classes allowed the development of students' mathematical abilities and the diversification of educational spaces.